Relative validity and reproducibility of a short semi-quantitative food frequency questionnaire for Chinese athletes. - Qian Xu; Yudan Chu; Huajun Tian; Guoqiang Ma; Jun Qiu; Qiuping Zhang (PLoS ONE)
A convenient but efficient tool for evaluating dietary intakes in Chinese professional athletes has yet to be established. The aim of this study was to assess the validity of a short semi-quantitative food frequency questionnaire (FFQ) through comparison with 3-day weighed food records (3DWFRs) and corresponding serum biomarkers from a cohort of 102 professional athletes, while also evaluating its reproducibility. The relative validity was assessed using Spearman correlation coefficients, cross-quintiles classification, weighted kappa, and Bland-Altman analysis, while reproducibility was evaluated using the Spearman correlation coefficients and intraclass correlation coefficient (ICC) between two FFQs. The results showed the median (range) crude correlation coefficients (CCs) between the first FFQ and 3DWFRs for energy and nutrients, and the food groups were 0.331 (0.219 to 0.568) and 0.292 (-0.035 to 0.455), respectively. Omega-3 polyunsaturated fatty acid (EPA, DHA, and EPA+DHA) intake estimated from the FFQ significantly correlated with corresponding serum biomarkers, with CCs ranging from 0.389 to 0.520. Weighted kappa statistics, indicating acceptable consistency (> 0.2) for most items, varied from -0.076 to 0.581, except for vitamin C, vegetables, and oils. Misclassification of nutrients and food groups into extreme quartiles was rare, with a median misclassification rate of 2% (ranging from 1% to 12%) and 3% (ranging 0 to 10%), respectively. Bland-Altman analysis revealed good agreement between FFQ and 3DWFRs, with over 90% of data points falling within the limits of agreement (LOA) for all assessed nutrients and food groups. In the reproducibility analysis, the median (range) crude CC and ICC for energy and nutrients were 0.574 (0.423 to 0.643) and 0.668 (0.558 to 0.763), respectively, while for food groups, they were 0.681 (0.242 to 0.764) and 0.640 (0.371 to 0.787), respectively. In conclusion, the short FFQ demonstrated acceptable relative validity and reproducibility for most nutrients and food groups, suggesting its potential as a valuable tool for assessing dietary intake and nutrition status among young Chinese athletes.